Introduction of "Sugar Tax" in South Africa: Placebo or panacea to curb the onset of cardio-metabolic diseases? - Benade, Janina; Essop, Faaidiel (SA Heart Journal, 2017)
During 2016 an announcement was made that South Africans will be obliged to pay a 20% “sugar tax’’ that will soon be implemented in order to help curb the rising prevalence of cardio-metabolic diseases. This announcement was met with mixed responses, with strong support from some quarters while others questioned whether it would indeed lead to improved health and well-being of South Africans. As sugar-sweetened beverages (SSBs) constitute a significant portion of added sugars in modern-day diets, it is firmly in the cross-hairs of the new taxation. This perspective article reflects on the proposed sugar tax by exploring the nature of SSB consumption patterns, evaluating epidemiological evidence associating SSB intake to cardio-metabolic diseases risk and by considering examples where a similar tax had previously been introduced. Here data reveal that there is robust evidence supporting a detrimental link between high SSB consumption patterns and the onset of cardiometabolic diseases. It is therefore our strong opinion that the sugar tax option should be pursued in parallel with well-designed, long-term studies to evaluate whether it decreases SSB intake and lowers the prevalence of cardio-metabolic diseases within the South African context.